Pengaruh Goodwill dan Aset Tak Berwujud Lainnya Terhadap Nilai Perusahaan - Lamuda, Ilyas; Karundeng, Deby Rita; Denisa, Deo (Jurnal Ekonomi, Manajemen, Ilmu Sosial dan Politik, 2026)
This research aims to determine the influence of goodwill on the value of companies listed on the Indonesian Sharia Stock Index, as well as the influence of other intangible assets on the value of companies listed on the Indonesian Sharia Stock Index. This study is expected to be beneficial to the field of science and to develop insights into the influence of goodwill and other intangible assets on company value. In this research, data from companies listed on the Indonesian Sharia Stock Index were collected through empirical data collection and literature review. The literature review method involved processing literature, articles, journals, and other written media related to the research topic. The aim is to support the discussion being studied and to gain theoretical understanding. This research uses a quantitative method. Hypothesis testing was conducted through the coefficient of determination adjusted R square (Adj R2), F test, and t test, with a total sample of 20 companies listed on the Indonesian Sharia Stock Index.